2012
DOI: 10.2176/nmc.52.488
|View full text |Cite
|
Sign up to set email alerts
|

Early Cerebral Circulatory Disturbance in Patients Suffering Subarachnoid Hemorrhage Prior to the Delayed Cerebral Vasospasm Stage: Xenon Computed Tomography and Perfusion Computed Tomography Study

Abstract: Subarachnoid hemorrhage (SAH) causes dynamic changes in cerebral blood flow (CBF), and results in delayed ischemia due to vasospasm, and early perfusion deficits before delayed cerebral vasospasm (CVS). The present study examined the severity of cerebral circulatory disturbance during the early phase before delayed CVS and whether it can be used to predict patient outcome. A total of 94 patients with SAH underwent simultaneous xenon computed tomography (CT) and perfusion CT to evaluate cerebral circulation on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 27 publications
3
14
0
2
Order By: Relevance
“…29,32 However, despite normal CPP, the early phase following SAH may be accompanied by a severe reduction in CBF, approaching ischemic levels as shown in patients and experimental animals. 23,24,27 Because large cerebral vessels were not spastic at this early time after SAH, perfusion deficits on the level of the cerebral microcirculation were the only mechanisms left to explain the observed cerebral ischemia. The degree of posthemorrhagic oligemia/ischemia was associated with an unfavorable outcome and high mortality.…”
Section: Microcirculatory Dysfunctionmentioning
confidence: 99%
See 3 more Smart Citations
“…29,32 However, despite normal CPP, the early phase following SAH may be accompanied by a severe reduction in CBF, approaching ischemic levels as shown in patients and experimental animals. 23,24,27 Because large cerebral vessels were not spastic at this early time after SAH, perfusion deficits on the level of the cerebral microcirculation were the only mechanisms left to explain the observed cerebral ischemia. The degree of posthemorrhagic oligemia/ischemia was associated with an unfavorable outcome and high mortality.…”
Section: Microcirculatory Dysfunctionmentioning
confidence: 99%
“…22 Recent clinical studies demonstrated a significant long-lasting reduction in CBF, independent of cerebral perfusion pressure, and occurring within the first day after SAH, that is, long before onset of delayed large artery vasospasm. 23,24 Other studies also failed to identify a consistent correlation between large artery vasospasm and ischemia in the parenchyma perfused by spastic arteries. 25,26 Hence, as Bederson et al 27 hypothesized already 20 years ago, posthemorrhagic ischemia may be caused by changes at the level of the cerebral microcirculation.…”
Section: Alternative Mechanisms Of Posthemorrhage Ischemiamentioning
confidence: 99%
See 2 more Smart Citations
“…18,30 Computed tomography perfusion (CTP) allows visualization of brain perfusion and has been applied in brain tumors, ischemic stroke, and aSAH. 1,4,10,12,14,15,[17][18][19]23,25,28,33,[36][37][38] A disadvantage of CTP is the exposure to radiation, which precludes its frequent use. This is reflected by available studies, in which CTP was performed once between Days 5 and 14, which represent the days with the highest probability of vasospasm occurrence.…”
mentioning
confidence: 99%